Pemberdayaan Masyarakat dalam Upaya Menjaga Pelestarian Lingkungan Berperspektif Ekologi di Bali - Manteus, Agus Joko (Journal Of Social Empowerment Publications, 2025)
The implementation of Community Service (PkM) is part of the Tri Dharma of Higher Education, aimed at enhancing human and environmental resources. This activity emphasizes the importance of preserving nature, particularly in addressing the negative impacts of plastic waste, which is increasingly prevalent in urban, rural, and mountainous areas. PkM is conducted due to the low awareness among rural communities about the effects of plastic waste on soil fertility, leading to decreased yields of coffee, cocoa, and tubers. Through direct socialization and education, it is hoped that rural communities will become more prudent in managing plastic waste. This activity is also expected to be published in an accredited journal and to raise awareness among the community about the importance of a harmonious relationship between humans and nature, in line with the Tri Hita Karana philosophy.